Influence of Polypyrrole Morphology on Gas Sensing. Issue 1 (1st May 2022) - Sood, Y; Pawar, V S; Mudila, H; kumar, A
Abstract: Polypyrrole with different morphologies has great impact over its properties such as concentration, time, high surface to volume ratio, dopants etc based on morphology has been discussed in this review. These Polypyrrole are potentially used for the sensing of various gases such as NO2, NH3, CO, H2 and CH4 gases. The influence of surface morphology, and doping of various PPy structures on gas sensing performance are extensively explained in this article such as roughness of films of PPy due to nature of counter ions influence the response of PPy films when used as sensitive layer, nanosheet structures has lowest LOD and improved response/recovery times. Furthermore, article focused upon various morphologies of PPy obtained with different methods and its influence in sensitivity is explained in this article. The sensitivity and response of PPy to various gases are also reviewed.